Comparative Approach to Organizational Communication in Conventional and Islamic Banking Systems - Leonard-Alin RIZOIU; Iolanda-Petronela GROSU; Cristina STATE; Dan POPESCU (Revista de Management Comparat International)
This paper conducts a comparative analysis of organizational communication strategies within conventional and Islamic banking systems, focusing on how these strategies influence operational efficiency, compliance, and stakeholder engagement within their distinct ethical and regulatory frameworks. Utilizing a qualitative research methodology, the study draws on secondary data from academic journals, industry reports, and specific case studies to explore the nuances of each system. The findings reveal that while conventional banks prioritize efficiency and profit maximization often facilitated by advanced technologies, Islamic banks emphasize ethical practices and transparency, guided by Sharia principles. These differences not only affect internal operations but also shape customer relationships and market perceptions. The paper concludes that integrating Islamic banking's ethical communication strategies into conventional banking could enhance global trust and compliance. This study suggests potential areas for further research, including the practical integration of these communication strategies across diverse banking environments, to foster a more inclusive and ethical global financial landscape.